Circulating calprotectin (S100A8/A9) is higher in rheumatoid arthritis patients that relapse within 12 months of tapering anti-rheumatic drugs - De Moel, Emma C.; Rech, Jürgen; Mahler, Michael; Roth, Johannes; Vogl, Thomas; Schouffoer, Anne; Goekoop, Robbert J.; Huizinga, Tom W.J.; Allaart, Cornelia F.; Toes, René E.M.; Schett, Georg; Van Der Woude, Diane (Arthritis Research & Therapy, 2019)
Objective: To investigate whether calprotectin (S100A8/A9 or MRP8/14), an inflammatory complex released by monocytes, could indicate residual subclinical inflammation in rheumatoid arthritis (RA) patients who are in stable remission on disease-modifying anti-rheumatic drugs (DMARDs) and serve as a marker for disease flare after DMARD tapering. Methods: We used data from two trials. Patients from the IMPROVED study had early (< 2 years) RA, and when they achieved disease activity score remission (DAS44 < 1.6), they stopped methotrexate to attempt drug-free remission. Patients from the RETRO study had established RA in stable remission (DAS28 < 2.6) and either tapered by 50% or stopped (biological or conventional) DMARDs. Circulating calprotectin at the tapering time point was determined by ELISA, and its predictive value for flare (loss of remission) within 12 months of DMARD tapering/stopping was determined. Results: In both IMPROVED (n = 104) and RETRO (n = 57), patients that flared within 12 months had higher calprotectin at the moment of DMARD tapering/stopping. Twofold higher calprotectin at the moment of DMARD tapering/stopping was associated with an increased risk (odds ratio) of flare of 1.07 (95% CI 0.98-1.18, p = 0.14) in the IMPROVED and 3.62 (95% CI 1.76-7.46, p < 0.001) in the RETRO. Correcting for clinical predictors of flare (DAS at study inclusion, anti-CCP2 positivity, gender) did not change these estimates. The area under the receiver operating curve of calprotectin levels for predicting flare within 12 months was 0.63 (95% CIs 0.51-0.76) in the IMPROVED study and 0.80 (95% CIs 0.69 to 0.92) in the RETRO study. Conclusion: Circulating calprotectin levels in RA patients in remission on DMARDs are higher in patients that will flare upon DMARD tapering/stopping. Since the differences between the cohorts precluded definitive conclusions, more research is needed to determine whether calprotectin has prognostic value in predicting flare after attempting drug tapering in RA. Trial registration: IMPROVED, ISRCTN11916566. RETRO, 2009-015740-42.
CRIS-Team Scopus Importer:2019-12-17
Keywords: Calprotectin; Disease activity; MRP8/14; Rheumatoid arthritis; S100A8/A9